Safety and efficacy of a feed additive consisting of chromium chelate of DL‐methionine (Availa® Cr) for salmonids (Zinpro Animal Nutrition Europe, Inc.) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Roberto Edoardo Villa; Giovanna Azimonti; Eleftherios Bonos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Ronette Gehring; Boet Glandorf; Maryline Kouba; Marta López‐Alonso; Francesca Marcon; et al. (EFSA Journal)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the safety and efficacy of a feed additive consisting of chromium chelate of DL‐methionine (Availa® Cr) for salmonids. The EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) concluded that the additive is safe for salmonids at the maximum recommended of 600 mg additive/kg complete feed (corresponding to 0.6 mg Cr/kg complete feed). The use of the additive in animal feed is considered safe for the consumers and the environment. The additive is not an eye nor skin irritant. Due to the presence of nickel, the additive is considered a skin and respiratory sensitiser. Inhalation and dermal exposure are considered a risk. The FEEDAP Panel concludes that the additive may have the potential to be efficacious in improving the performance of salmonids at 200 mg additive/kg complete feed (0.2 mg Cr/kg complete feed).